Effect of three different between-inning recovery methods on baseball pitching performance - Warren, C. D.; Brown, L. E.; Landers, M. R.; Stahura, K. A. (The Journal of Strength and Conditioning Research, 2011)
A decrease in blood hydrogen ions (H+) may allow for the recovery of a muscle, which should allow for greater performance in subsequent activity. The purpose of this study was to determine which of 3 forms of recovery were the most effective after an inning of pitching in baseball. Three different measurements were used to determine which recovery method was most effective; the difference in blood lactate (BLa) levels was used as a biological measurement, average pitching speed was the physiological measurement, and the psychological measurement was done on how the pitchers perceived their pitching and recovery. The recovery methods that were used were passive recovery (PR), active recovery (AR), and electromuscular stimulation (EMS). Seven college men aged 21 (±2 years) who were National Collegiate Athletic Association Division II college baseball pitchers were assessed during game play simulations. Blood lactate levels decreased significantly from the premeasurement to the postmeasurement with the EMS recovery method (p < 0.0005); however, BLa did not change for PR (p = 0.017) or AR (p = 0.134). Perceived recovery was also found to be best in the EMS and PR conditions. These findings suggest that EMS is an effective recovery method between innings of pitching.